The effect of group vocal and singing exercises for individuals with Parkinson's disease - Philippe, Anna, author; LaGasse, Ashley Blythe, advisor; Knight, Andrew, advisor; Fails, Anna Dee, committee member (Colorado State University. Libraries, 2020)
The majority of individuals with Parkinson's disease (PD) experience voice and speech deficits, collectively called hypokinetic dysarthria; however, treatment outcomes are inconsistent and often unsustainable. The purpose of this study was to replicate the music therapy protocol for hypokinetic dysarthria (MTPHD) completed by Azekawa and LaGasse (2018) in an effort to investigate the effects of a group music therapy treatment for individuals who exhibited voice and speech deficits due to PD. The MTPHD consisted of three neurologic music therapy (NMT) techniques that specifically target voice and speech characteristics. A total of 17 participants with PD completed eight weekly group music therapy sessions. Pretest and posttest measurements were documented for three speech assessments to address vocal function, vocal quality, articulatory control, and connected speech intelligibility. Significant differences were found in vocal quality and the number of inter-word pauses. Positive trends were observed in all other measurements, indicating that music therapy may be a viable treatment option to address hypokinetic dysarthria in persons with PD.
Keywords: music; voice; music therapy; hypokinetic dysarthria; speech; Parkinson's disease